EVA/zinc oxide nanocomposites for active food packaging: selected physical, and microbial properties - Haza Satar Majeed; Farah Khalaf Hammoud Al-Juboory; Raghad Hamid; Ruzniza Mohd Zawawi (Polimery)
The melt-mixing method was used to obtain nanocomposites of ethylene vinyl acetate copolymer (EVA) with 1, 3 or 5wt% of hydrophilic zinc oxide (ZnO) nanoparticles. The contact angle, barrier and antimicrobial properties of the obtained composites were investigated. The nanocomposites were characterized by better hydrophilic and barrier properties, as evidenced by, respectively, a smaller contact angle and lower water vapor permeability and water absorption compared to EVA, which can be explained by the formation of hydrogen bonds between EVA and ZnO. In addition, the composites were characterized by greater bactericidal activity against E. coli and S. aureus. The optimal physical and microbial properties were obtained with 3 wt% ZnO content.